Tes Diagnostik Four-Tier untuk Mengidentifikasi Miskonsepsi pada Materi Fisika - Paramitha, Diyen; Maison, Maison; Darmaji, Darmaji (Jurnal Penelitian Pendidikan Fisika, 2021)
In physics learning, the ability to understand concepts is an important indicator, but in fact one of the problems found is that there are still students who experience misconceptions. Misconception refers to a concept that is incompatible with the scientific understanding accepted by experts. This article as a literature review aims to find out the misconceptions experienced by students in some physics material. This research method is a national literature review article for the years 2017-2020 which is in accordance with the researcher's keywords. Based on the results of the literature review, there are still students who experience misconceptions on geometric optical material by 37.62% (intermediate level), thermodynamics at 28.04% (low level), effort and energy by 24% (low level), dynamic fluid by 29 ,21%, Mechanical Waves by 26.9%. Misconceptions cannot be known directly so it is necessary to carry out a diagnostic test that can distinguish students who understand concepts, do not understand concepts and those who do not. There are many ways that can be used to identify misconceptions, one of which is using a four-tier diagnostic test.